2010
DOI: 10.1017/s1041610210000281
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of neuropsychiatric symptoms and psychiatric disorders in mild Alzheimer's disease and mild cognitive impairment subtypes

Abstract: Clinicians should consider the relevance of neuropsychiatric disorders and symptoms in patients with cognitive disturbances, and incorporate a thorough psychiatric examination in the evaluation of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 41 publications
7
79
1
1
Order By: Relevance
“…Our study identified a high frequency and severity of depression in the very early stage (CDR = 0.5) of dementia patients, similar to previous findings 23 . It is possible that symptoms are associated with pathological changes in regions of the brain associated with its pathogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Our study identified a high frequency and severity of depression in the very early stage (CDR = 0.5) of dementia patients, similar to previous findings 23 . It is possible that symptoms are associated with pathological changes in regions of the brain associated with its pathogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…[73][74][75] There is a growing tendency to admit that neuropsychiatric symptoms may accelerate the transitional state from MCI to dementia. 74,75 These symptoms could confer a higher risk for dementia even among cognitively preserved persons. 73 Accordingly, neuropsychiatric symptoms now tend to be incorporated into any comprehensive clinical examination of individuals with MCI.…”
Section: Neuropsychiatric Symptoms and Risk Of Cognitive Declinementioning
confidence: 99%
“…Most of the studies on NPS to date have focused on highly selective clinical samples recruited from tertiary care centers [12,[23][24][25] or as subsamples of population-based cohorts [4,7,8,14,19,26]. This means that there is a gap in our knowledge about the spectrum of NPS occurring in the population across different cognitive phenotypes, disorders, outcomes, and status.…”
Section: Introductionmentioning
confidence: 99%